Psychological analysis of extreme situations in the professional activity of the employees of the State Penitentiary Service of Ukraine - O. V. Timchenko (Law and Safety)
The specifics of professional activity of the employees of the State Penitentiary Service of Ukraine (SPS of Ukraine) have been revealed. It has been noted that specific features of professional activity of the employees of the State Penitentiary Service of Ukraine are due to: specific conditions of official activity; shortcomings in the organization of official activities; the presence of risk; constant communication with convicts; the occurrence of negative personal changes of employees; the presence of conflict interaction between the various services of penitentiary institutions.